Systematization and Formalization of Passive Monitoring Data in Accordance with the Component-Functional State of Heat Supply Systems (Economics and region, 2020)
The article examines the assessment of the state of water and hot heat supply systems of heat and power facilities for innovative and constructive use of thermal energy, with effective use in all areas of these systems: generation, for heating water or for generating steam, transporting it to the consumer, as well as when it is consumer so rich industries. Including the housing and communal complex and the construction industry – for example, a scientific and methodological concept has been created for the implementation of passive monitoring to assess the state of heat supply systems, under the conditions of the initial action, on material flows in them of electromagnetic fields. It has been established that an effective form of reagent-free water preparation in electromagnetic fields is technogenic – the nature of material flows due to the electromagnetic dissociation of their micro particles and the formation of active complexes (due to the interaction between them) is determined. It has been established that as a result of passive monitoring, the systematization and formalization of its data should be carried out taking into account three aspects: engineering - technological, engineering – microbiological and organizational – managerial decisions. It is shown that the passive monitoring system is an obligatory subordinate component of environmental management in the industrial sphere – heat and power facilities of water and steam heat supply systems of an innovative direction. The analysis of the content of the point of view of Ukrainian and foreign scientists, monographs is carried out and joint conclusions are made in the conditions of the illuminated literary material under the following headings: the main economic, environmental and regulatory aspects of nature management; the formation of the biosphere in the conditions of transformation of its individual components; methods of environmental management and environmental policy and the like. In these conditions, the formation of an effective economic mechanism for environmental management is of priority; on the central issue of integral management, it requires clarification – formalization of parameters should be considered effective, which make it possible to clarify a compromise between economic development and environmental safety. It is the economic and environmental analysis of the components of technological processes that makes it possible to establish the limiting factors of development in the system (action – state – improvement) and to determine individual patterns (tendencies) in order to overcome them. The theoretical principles of magnetized water are presented in the works, and the priority level is confirmed by the receipt of three patents of Ukraine for useful action and one copyright certificate for intellectual property, and received support at domestic and foreign conferences. The proposed levers improve integral control in the process of modernizing the technology of non-reagent water treatment (use of electromagnetic fields) at heat and power facilities of rich operating industries and make it impossible to process environmental pollution and save energy costs with effective continuous planning of new facilities. Therefore, through the analysis of the general environmental situation, the technical state of the initial data systems, it is possible to confirm the developed classification and formalization of passive monitoring data, on the use of theoretical foundations in practice – the regulations for industrial implementation, is the basis of the concept of sustainable development.
Keywords: sustainable development; heat supply; passive monitoring; environmental protection